1) Calcule:
1) (+). ( + )
2)(-):(-3)
3) (+3)(-3)
4) (+9):(+) =
5) (-3).(+3) =
6) (-3).(-3) =
7) (+2).(-3).(+3) =
8) (+3):(-3) -
9) (-3):(-) =
10) (+):(-3) =
11) (-3):(-1) =
12) (+3)+(-3) =
13) (-3):(-) =
Potenciação e radiciação
Respostas
respondido por:
0
Explicação passo-a-passo:
1) (+). ( + ) = +
2)(-):(-3) = 3
3) (+3)(-3) = -9
4) (+9):(+) = 9
5) (-3).(+3) = -9
6) (-3).(-3) = 9
7) (+2).(-3).(+3) = -18
8) (+3):(-3) = -1
9) (-3):(-) = 3
10) (+):(-3) = -3
11) (-3):(-1) = 3
12) (+3)+(-3) = 0
13) (-3):(-) = 3
Perguntas similares
4 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás